Borderlands in Museum Narratives in the Federation of Bosnia and Herzegovina - Baczyński, Maciej Adam (Mundus Slavicus I, 2025)
The category of borderlands is growing in importance. In the following text, it is used to examine museum narratives in the Federation of Bosnia and Herzegovina. Museums use it to present the history of territories, but also the lives and experiences of individuals. Although many museums strive to objectify the content they provide, they often emphasize the Bosniak perspective. The article is based on field research (content analysis of museum exhibitions, participant observation, and semi-structured interviews with employees) conducted in museums in Bosnia and Herzegovina since the beginning of 2022.